2020
DOI: 10.1111/jcmm.15423
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Notch1 pathway induces peripartum cardiomyopathy

Abstract: Increased expression and activity of cardiac and circulating cathepsin D and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) have been demonstrated to induce and promote peripartum cardiomyopathy (PPCM) via promoting cleavage of 23‐kD prolactin (PRL) to 16‐kD PRL and neutralizing vascular endothelial growth factor (VEGF), respectively. We hypothesized that activation of Hes1 is proposed to suppress cathepsin D via activating Stat3, leading to alleviated development of PPCM. In the present study, we aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…At the same time NP-6A4-AT2R signaling increases expression of Notch1 and EPO that promote cardiac repair. Notch1 signaling is activated in response to myocardial injury and is involved in suppression of cardiomyocyte apoptosis, cardiac repair and regeneration (Li et al, 2010;Yu and Song, 2014;Zhu et al, 2020). Erythropoietin (EPO) increases myocardial performance and induces cardiac repair after myocardial infarction (Santhanam et al, 2010;Zafiriou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time NP-6A4-AT2R signaling increases expression of Notch1 and EPO that promote cardiac repair. Notch1 signaling is activated in response to myocardial injury and is involved in suppression of cardiomyocyte apoptosis, cardiac repair and regeneration (Li et al, 2010;Yu and Song, 2014;Zhu et al, 2020). Erythropoietin (EPO) increases myocardial performance and induces cardiac repair after myocardial infarction (Santhanam et al, 2010;Zafiriou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac levels of two molecules implicated in cardiac repair, Erythropoietin (EPO) (Santhanam et al, 2010;Zafiriou et al, 2014)) and Notch1 (Yu and Song 2014;Zhu et al, 2020;Li et al, 2021) were significantly increased by NP-6A4 in ZO rat heart (Figure 5A). Thus, NP-6A4 increased the expression of at least three cardioprotective molecules in the ZO rat heart, namely, AT2R, EPO and Notch1.…”
Section: Np-6a4 Treatment Increased the Expression Of Cardioprotective Erythropoietin (Epo) And Notch1 In Addition To The Reparative At2rmentioning
confidence: 99%
“…Treatment of pregnant wild-type mice during the last 3 days of gestation and first 3 weeks postpartum with an inhibitor of γ-secretase, which is required to activate Notch1 and normal angiogenesis, led to systolic cardiac failure, accompanied by blunted angiogenesis and lower circulating levels of cathepsin D and of sFlt1. 127 The study did not elucidate if γ-secretase inhibition elicits this cardiac phenotype primarily by acting on endothelial cells (where Notch1 plays a strong role) versus in cardiomyocytes (where cathepsin D is regulated) versus the placenta (the primary source of sFlt1 during pregnancy). Known effects of γ-secretase inhibition beyond suppression of Notch1 may also have contributed to the phenotype.…”
Section: Pharmacological Compoundsmentioning
confidence: 98%
“…Notch signaling may inhibit CMC hypertrophy [ 5 , 44 ]. Thus, it has been shown that the inhibition of the Notch1-Hes1 axis by a γ-secretase inhibitor (LY-411575) results in the increased expression of hypertrophic genes (ANP, BNP and β-MHC) [ 45 ]. “Created with BioRender.com”.…”
Section: Role Of the Notch Signaling Pathway In Myocardial Infarctionmentioning
confidence: 99%